Tuning the controller gains using sensitivity analysis - Pal A.K.; Kumar S.; Kamal S.; Leung H.; Xiong X. (My University, 2025)
This paper tries to solve the general problem of controller gain tuning. To that end, sensitivity analysis has been utilized. The study provides vital results to extend the usage of sensitivity analysis for the class of finite-time stable dynamics. The controller gain tuning procedure is elaborated by considering the examples of state feedback control and predefined time control. An insight into the selection of the gains or system parameters for these class of systems is presented with the help of sensitivity analysis. The sensitivity of the solution for these class of systems with the variation in the gains or system parameters is studied. Having know-how about the adjustment of these system gains or parameters will be beneficial from the point of view of practical applications. Thus, the proposed approach finds utility in controller gain tuning, which is an important aspect of control design. © 2024 Chinese Automatic Control Society and John Wiley & Sons Australia, Ltd.